Pendekatan pembelajaran berasaskan simposium: mengasah pemikiran kritis dan komunikasi dalam melahirkan graduan kompetitif - Wan Fathul Hakim W Zamri; Nurhasyimah Aziz; Muhamad Faiz Md Din; Azhari Shamsudeen (Penerbit Universiti Kebangsaan Malaysia, 2024)
The symposium was implemented as a strategy to strengthen communication and critical thinking skills among mechanical engineering students, with the aim of producing competitive graduates. Competitive graduates are closely related to graduate employability because of the characteristics they possess, such as mastering technical skills, soft skills, and adaptability to change which can increase their chances of employment. Therefore, this study explores an alternative learning approach, namely the symposium-based learning approach. This paper explains in detail the implementation process of this symposium which has two phases, namely Phase I – organizing the symposium (CTME2024) and Phase II – publication. The theme of the symposium focuses on the latest topics of engineering. The symposium provided an opportunity for students to present their research findings, exchange ideas, as well as receive constructive feedback from peers, lecturers, and industry panelists which indirectly enhanced their confidence and communication skills. The added value of graduates can be increased because it integrates active learning elements such as presentations, discussions, and academic interaction. The results of the study showed a significant improvement in students' communication skills and critical thinking through these activities. In fact, the abilityof the articles produced by students to be successfully published in MyCite-indexed journals gives a positive signal to the goal of producing competitive graduates. The implications of this study suggest that the integration of symposiums in the mechanical engineering curriculum can be an effective strategy to empower graduates.